Advanced Theranostic Nanomedicine in Oncology - Ciofani, Gianni; Marino, Attilio; Tapeinos, Christos (Frontiers Media SA, 2020)
Despite the vast and increasing scientific literature on the treatment of malicious diseases such as cancer, we are still far to accomplish most of the current unmet clinical desiderata. A special interest in the biomedical field has been recently directed towards "theranostic" devices, aiming at combining diagnostic and therapeutic functionalities into a single platform, and thus enabling both early detection of the pathology and its focused and targeted treatment. This Research Topic deals with the synthesis and the physicochemical characterization of theranostic agents at the nano- and/or micro-scale, as well as with their biological and medical evaluation for potential future applications.